valuation on the Customer Satisfaction Towards the Service Quality of Selected Stalls at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study evaluates the customer satisfaction towards the service quality of selected stalls atBestlink College of the Philippines in terms of tangible, reliability, responsiveness, andassurance; the significant relationship between and among the service quality and itscustomer satisfaction in terms of aforecited variables; issues do people have with the selectedstalls that they can complain about in terms of their customer service; and proposedrecommendations to address the following concerns in attaining the service quality oncustomer satisfaction.The results of this study reveal that the evaluation of customer satisfaction with the servicequality of selected stalls is evaluated as strongly agreed upon in terms of tangible, reliability,responsiveness, and assurance; the issue with the food stalls in terms of customer service isthat no availability of seats.This study recommended that to prevent customers from getting fed up with the food they buyand to ensure that the food they serve is fresh rather than just reheated, sell freshly cookedand nutritious one to attract a lot of customers. This action will help the stalls to maintain andgive the best of what customers want and make them satisfied.
Keywords: Business